Development and application of an optimization model for elite level shot putting - Young, M. (2009)
The purpose of this study was to test the affects of a technical intervention based on a previously developed optimization model on an athlete`s competition performance. The results indicate that a technical intervention produces meaningful changes in kinematics and performance not observed in a NTI group but the kinematic changes are not necessarily in agreement with the OMPs suggested in the technical intervention. This study provides important information to coaches and elite female shot putters and provides direction for future biomechanical research on this event. Future research should focus on both refining understanding of the current OMPs, individualizing the OMPs to each athlete, examining the trunk whip phenomenon in greater depth, and finding any parameters that may have been omitted. Continued research is also needed to determine the best means of disseminating information to coaches and athletes to most effectively produce beneficial change in the OMPs.